Manajemen Sumber Daya Manusia Dalam Lembaga Pendidikan Islam - Nasiruddin, Nasiruddin - (FDIK IAIN Padangsidimpuan, 2023)
Issues related to human resources (HR) have become a major highlight in the world of work and community development today. Human resources (HR) is one of the most important aspects of life. In essence, human resources are people who are employed in the organization as movers, thinkers and planners to achieve organizational goals. Therefore, human resources are very important and need to be managed effectively. As for this study, it aims to describe contemporary issues related to human resources (HR) in educational institutions. This research uses a type of descriptive qualitative research, with a literature review approach. This study examines teacher certification and its problems, human resources and universities in the era of globalization, teacher performance assessment and continuous professional development (PKG) and strengthening the competence of school administrators and supervisors.